1995
DOI: 10.1063/1.114815
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced superparamagnetism in two-dimensional arrays of nanometer-sized Fe islands

Abstract: Iron grown on room-temperature CaF2/Si(111) substrates form two-dimensional arrays of nanometer-sized superparamagnetic islands. Deposition of Ag on the Fe/CaF2/Si(111) produced a superparamagnetic response where the effective moment was proportional to the number of Fe islands covered by an average-sized Ag island. The nonmagnetic Ag overlayer mediates a long-range exchange between neighboring Fe islands within an individual Ag island. Monte Carlo methods are used to examine ordering in two dimensions and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Investigation of magnetic nanodot systems have shown a transition from a superparamagnetic regime to a super spin-glass state, and addressed evidences for a transition to a superferromagnetic (SFM) order [5,6]. As far as we know evidences of the SFM ordering was first addressed on goethite nanodots [7], but it has been recently found on several systems containing MNDs deposited on metallic or insulator non-magnetic substrates [4][5][6][7][8][9][10][11][12][13][14][15][16]. It has been pointed out in the literature that such a transition can be achieved through dipole-dipole interaction [4] or through an exchange coupling between the magnetic nanodot moments [5,11,17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of magnetic nanodot systems have shown a transition from a superparamagnetic regime to a super spin-glass state, and addressed evidences for a transition to a superferromagnetic (SFM) order [5,6]. As far as we know evidences of the SFM ordering was first addressed on goethite nanodots [7], but it has been recently found on several systems containing MNDs deposited on metallic or insulator non-magnetic substrates [4][5][6][7][8][9][10][11][12][13][14][15][16]. It has been pointed out in the literature that such a transition can be achieved through dipole-dipole interaction [4] or through an exchange coupling between the magnetic nanodot moments [5,11,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, two-dimensional (2D) ordered magnetic nanodot (MND) configurations can be experimentally realized by combining molecular beam epitaxy with high-resolution lithography techniques, leading to different arrangements of large spin dots [3,4]. Investigation of magnetic nanodot systems have shown a transition from a superparamagnetic regime to a super spin-glass state, and addressed evidences for a transition to a superferromagnetic (SFM) order [5,6]. As far as we know evidences of the SFM ordering was first addressed on goethite nanodots [7], but it has been recently found on several systems containing MNDs deposited on metallic or insulator non-magnetic substrates [4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…With the trials of Fe/Cu(100) still fresh in our minds, we realized that we needed to focus on magnetic systems that played to the obvious strength of MIDAS, unparalleled transverse spatial resolution. We shifted to small particle magnetism, specifically order-disorder transitions induced by geometrical ordering on surfaces on nm-length scales [63][64][65][66]. CaF 2 /Si(111) was selected as a technologically relevant material, one that should yield small islands of transition metal (Fe, Co) on the insulator, and, perhaps might be patterned in-situ.…”
Section: Applications To Magnetic Materialsmentioning
confidence: 99%
“…Locally modifying the surface of the CaF 2 using the electron beam in MIDAS, producing Ca-rich areas, might more effectively nucleate the transition metal deposit. Important results were obtained on random 2D particulate magnetism [63][64][65], and it was convincingly shown that film growth was dominated by defect nucleation [66]. Our efforts to produce lithographically defined structures in-situ stopped at that point, and further progress was not made until Akira Sugawara arrived as a postdoctoral fellow, and introduced us to his NaCl(110) reconstructed surface-templates.…”
Section: Applications To Magnetic Materialsmentioning
confidence: 99%
“…6,7 The electronic conduction in 2D structures acquires added significance if the islands are magnetically ordered, which brings in the importance of the inter-and intraisland spin polarized transport. 8 While the flow of current in three-dimensional ͑3D͒ granular systems consisting of ferromagnetic and nonmagnetic metal clusters dispersed in dielectric host has been addressed extensively, 9 work on 2D systems is limited primarily to quenchedcondensed ultrathin films 8,[10][11][12][13][14] or self-assembled dot superlattices, 15,16 which give the structure a partial 3D character.…”
Section: Introductionmentioning
confidence: 99%